Anodic bondable Li-Na-Al-B-Si-O glass-ceramics for Si - ULTCC heterogeneous integration. Issue 7 (July 2019) - Chen, Guanyu; Ma, Mingsheng; Liu, Zhifu; Wei, Anqing; Zavabeti, Ali; Hu, Xinyi; Zhang, Faqiang; Wang, Bing; Mitchell, Arnan; Li, Yongxiang
Graphical abstract: Abstract: In this paper, we report an anodic bondable Li-Na-Al-B-Si-O (LNABS) glass-ceramic system with a low temperautre (150 °C) and voltage (200 V) for Si - ULTCC (Ultra-Low Temperature Co-fired Ceramics) heterougeneous integration. The ULTCC materials are predominantly composed of multicrystalline LiAlSi2 O6 with a small amount of glass phase. The coefficient of thermal expansion (CTE) of LNABS is 3.27 ppm/°C (25–300 °C) leading to excellent theraml compatibility with silicon wafer over a wide temperature range from 60 °C to 300 °C. To demonstrate the utility of this system, a silicon micro-electro-mechanical (MEMS) systems pressure sensor is encapsulated between silicon and ULTCC substrates. This sensor exhibits high accuracy and good stability in the temperature range from −40 °C to 120 °C. The bonding current, cross section and alkali ions concentration were investigated, and the anodic bonding mechanism at low temperature and voltage was revealed. The alkali ions migrate through the glass phase due to its lower activation energy, which also forms a high space-charge electric field at the bonding interface. The non-bridge oxygen (NBO) drifts towards silicon and oxidized silicon under high space-charge electric field. The calculated diffusion coefficient of NBO indicates that the elevated temperature and voltage both benefit the migration of NBO. These finding illustrate the great potential of LNABS glass-ceramic for high quality microelectronic and MEMS packaging technology with advantages of multilayer structure, low anodic bonding temperature and voltage, as well as the excellent theraml compatibility with Si wafers.